Hidden Wounds? Inflammatory links between childhood trauma and psychopathology. [article]. - Danese, Andrea
Childhood trauma is a key risk factor for psychopathology. However, little is known about how exposure to childhood trauma is translated into biological risk for psychopathology. Observational human studies and experimental animal models suggest that childhood exposure to stress can trigger an enduring systemic inflammatory response not unlike the bodily response to physical injury. In turn, these ?hidden wounds? of childhood trauma can affect brain development, key behavioral domains (e.g., cognition, positive valence systems, negative valence systems), reactivity to subsequent stressors, and, ultimately, risk for psychopathology. Further research is needed to better characterize the inflammatory links between childhood trauma and psychopathology. Detecting and healing these hidden wounds may help prevent and treat psychopathology emerging after childhood trauma. -- (from the author)
Keywords: Childhood trauma; Maltreatment; Psychopathology; Psychiatric disorders; Inflammation